2018
DOI: 10.1002/nau.23765
|View full text |Cite
|
Sign up to set email alerts
|

Determining integrity of bladder innervation and smooth muscle function 1 year after lower spinal root transection in canines

Abstract: Bladder smooth muscle cells maintain their function after long-term bladder decentralization. While pelvic plexus-induced bladder contractions were less robust at 1 year after lower spinal root transection, the absence of atrophy and preservation of at least some nerve activity may allow for successful surgical reinnervation after long-term injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 12 publications
(14 reference statements)
6
18
0
Order By: Relevance
“…Future experiments in bladder decentralization animal models should transect the dorsal root of L7 in addition to all sacral roots to achieve more complete decentralization of the bladder from lower lumbar and sacral spinal cord segments, as performed recently for acute bladder decentralization studies, 10 and for 1 year decentralization studies in which bladder integrity and contractility was examined. 12 We have reported that the rerouting procedures did not disrupt sympathetic projections to the bladder from caudal mesenteric ganglia. 13 We extend those results here to report that numbers of labeled neurons projecting to the urethral sphincter and bladder from sacral STG were significantly lower (yet not absent) in sacral decentralized groups compared with sham/unoperated controls.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Future experiments in bladder decentralization animal models should transect the dorsal root of L7 in addition to all sacral roots to achieve more complete decentralization of the bladder from lower lumbar and sacral spinal cord segments, as performed recently for acute bladder decentralization studies, 10 and for 1 year decentralization studies in which bladder integrity and contractility was examined. 12 We have reported that the rerouting procedures did not disrupt sympathetic projections to the bladder from caudal mesenteric ganglia. 13 We extend those results here to report that numbers of labeled neurons projecting to the urethral sphincter and bladder from sacral STG were significantly lower (yet not absent) in sacral decentralized groups compared with sham/unoperated controls.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, sacrally decentralized animals showed similar numbers of labeled neurons in L7 DRG as sham control animals. Future experiments in bladder decentralization animal models should transect the dorsal root of L7 in addition to all sacral roots to achieve more complete decentralization of the bladder from lower lumbar and sacral spinal cord segments, as performed recently for acute bladder decentralization studies, and for 1 year decentralization studies in which bladder integrity and contractility was examined …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In preclinical in vivo studies, the neural control of tissues or organs has been generally assessed by electrical stimulation of the major nerve innervating the region of interest. Functional reinnervation of bladder was evaluated in canine models of SCI by electrical stimulation of the pelvic plexus followed by monitoring detrusor muscle contraction and increase in bladder pressure 244,245 . In musculoskeletal traumarelated studies, reinnervation of injured muscle was assessed by measuring isometric muscle contraction force upon neural stimulation along with monitoring changes in gait pattern over time 246 .…”
Section: Challenges and Advancements Towards Fabricating Innervated Tmentioning
confidence: 99%